Every grain of sand : Canadian perspectives on ecology and environment - Wainwright, J. A., 1946- (Wilfrid Laurier University Press, 2004)
Annotation Combining personal memoirs with formal essays, this collection encourages activism as a personal commitment, dialogue with perceived enemies in environmental wars, and the dismantling of power-based divisions of centre versus marginal politics.
Keywords: Nature -- Effect of human beings on.; Human ecology.; Environmental degradation.; Human ecology -- Canada.; Environnement -- Dégradation.; Écologie humaine -- Canada.; Écologie humaine.; Êtres humains -- Influence sur la nature.; human ecology.; SOCIAL SCIENCE -- Human Geography.; Environmental degradation; Human ecology; Nature -- Effect of human beings on; Canada